2022
DOI: 10.3389/fmicb.2021.798350
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Bacillus subtilis ATCC19659 to Broiler Chickens Enhances Growth Performance and Immune Function by Modulating Intestinal Morphology and Cecum Microbiota

Abstract: This study investigated dietary supplementation with Bacillus subtilis (BS) ATCC19659 on growth performance, biochemical indices, intestinal morphology, and cecum microflora in broiler chicks. A total of 600 Arbor 1-day Acres broilers of either sex were allotted to 5 treatments: chicks were fed a corn- and soybean-based diet (CON); chicks were fed basal diet containing 500 mg ZnB/kg (ZnB); chicks were fed basal diet containing 1 × 108 CFU/g feed of BS-ATCC19659 (BS-1); chicks were fed basal diet containing 3 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 61 publications
(92 reference statements)
8
11
1
Order By: Relevance
“…For instance, Zhang et al demonstrated that Bacillus subtilis PB6 administration dramatically increased villus height and maintain intestinal mucosal barrier function of ducks (41). Analogously, Mohamed et al found that Bacillus subtilis administration in the basal diet could dramatically enhance the growth performance of broiler chickens by regulating gut microbiota and intestinal morphology (42). However, most of the present studies focus on the beneficial mechanism of probiotics on the host and few research pay attention to the genomic characteristics of probiotics.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, Zhang et al demonstrated that Bacillus subtilis PB6 administration dramatically increased villus height and maintain intestinal mucosal barrier function of ducks (41). Analogously, Mohamed et al found that Bacillus subtilis administration in the basal diet could dramatically enhance the growth performance of broiler chickens by regulating gut microbiota and intestinal morphology (42). However, most of the present studies focus on the beneficial mechanism of probiotics on the host and few research pay attention to the genomic characteristics of probiotics.…”
Section: Discussionmentioning
confidence: 98%
“…Eisenbergiella can play an important role in the synthesis of butyric acid, which is bene cial to the growth of intestinal epithelial cells [28]. Paraprevotella, Papillibacter, and Butyricimonas were associated with butyrate generation in the intestine, which was favorable to performance of chickens [29][30][31]. Moreover, unclassi ed_c__Clostridia has been implicated in the biosynthesis of SCFA [32].…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus species are the most commonly used probiotic microorganisms in animal production. Dietary supplementation with B. subtilis or B. licheniformis can enhance growth performance and mitigate C. perfringens -induced necrotic enteritis in broilers ( Knap et al, 2010 ; Abudabos et al, 2013 ; Gong et al, 2018 ; Hussein et al, 2020 ; Mohamed et al, 2022 ). Both B. subtilis and B. licheniformis show some similarities with antibiotic growth promoters in terms of improving growth performance in broilers ( Musa et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus species–based probiotics are the most commonly used probiotics in animal production because of their sporulation ability, which enables their survival under harsh environmental conditions (low pH, bile salts, and heat), spore germination in the gastrointestinal tract, and production of antimicrobial substances ( Ramlucken et al, 2020 ). Bacillus species–based probiotics can promote animal growth and prevent pathogenic infections in poultry ( Abudabos et al, 2013 ; Abudabos et al, 2017 ; Grant et al, 2018 ; Mohamed et al, 2022 ). Our previous studies have demonstrated that antimicrobial substances derived from fermented products obtained from Bacillus species ( B. subtilis or B. licheniformis ) can inhibit the growth of pathogens, particularly gram-positive bacteria ( Horng et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%